In Vivo and in Vitro Characterization of the Angiogenic Effect of CTX0E03 Human Neural Stem Cells. Issue 9 (September 2013) - Hicks, Caroline; Stevanato, Lara; Stroemer, Robert P.; Tang, Ellen; Richardson, Sheila; Sinden, John D.
CTX0E03 is a human neural stem cell line previously reported to reduce sensory motor deficits in a middle cerebral artery occlusion (MCAo) model of stroke. The objective of this study was to investigate if CTX0E03 treatment promotes angiogenesis. As stroke leads to damage of the vasculature in the brain, angiogenesis may contribute to the functional recovery. To test this hypothesis, the angiogenic activity of CTX0E03 was assessed both in vitro and in vivo. In vitro, CTX0E03 expression of trophic and proangiogenic factors was determined by real-time RT-PCR, Western blot, and ELISA, and its angiogenic activity was investigated in well-established angiogenesis assays. In vivo, angiogenesis was investigated in naive mice and MCAo rat brain and was evaluated by immunohistochemistry (IHC) using Von Willebrand factor (VWF), a marker of blood vessel formation, and BrdU/CD31 double labeling in naive mice only. In vitro results showed that CTX0E03-conditioned medium and coculture significantly increased total tubule formation compared with controls ( p = 0.002 and p = 0.0008, respectively). Furthermore, CTX0E03 cells were found to be in direct association with the tubules by ICC. In vivo CTX0E03-treated brains demonstrated a significant increase in areas occupied by VWF-positive microvessels compared with vehicle-treated naive mice (two-way ANOVA, Interaction p < 0.05, Treatment p < 0.0001, Time p < 0.0) and MCAo rat ( p = 0.001 unpaired t test, Welch's correction). CTX0E03-treated naive mouse brains showed an increase in BrdU/CD31 colabeling. In conclusion, in vitro CTX0E03 cells express proangiogenic factors and may promote angiogenesis by both release of paracrine factors and direct physical interaction. Furthermore, in vivo CTX0E03-treated rodent brains exhibited a significant increase in microvessels at the site of implantation compared with vehicle-injected groups. Taken together these data suggest that CTX0E03 cell therapy may provide significant benefit to stroke patients through upregulation of angiogenesis in the ischemic brain.